2019
DOI: 10.1097/ccm.0000000000003638
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam Dose Optimization in Critically Ill Pediatric Patients With Acute Respiratory Failure: A Population Pharmacokinetic-Pharmacogenomic Study

Abstract: Objective: To develop a pharmacokinetic-pharmacogenomic (PK-PG) population model of morphine in critically ill children with acute respiratory failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 84 publications
1
11
0
Order By: Relevance
“…Such frequent use of esketamine as a substance rarely used in modern intensive care was similarly found in another study [2]. For effective sedation with midazolam, a mean dosage of 0.15 (±0.1) mg�kg -1 �h -1 was found necessary in several studies [31][32][33][34]. In our patient cohort, midazolam was used at a similar mean dosage 0.14 (±0.10) mg�kg -1 �h -1 to obtain prescribed sedation.…”
Section: Plos Onesupporting
confidence: 77%
“…Such frequent use of esketamine as a substance rarely used in modern intensive care was similarly found in another study [2]. For effective sedation with midazolam, a mean dosage of 0.15 (±0.1) mg�kg -1 �h -1 was found necessary in several studies [31][32][33][34]. In our patient cohort, midazolam was used at a similar mean dosage 0.14 (±0.10) mg�kg -1 �h -1 to obtain prescribed sedation.…”
Section: Plos Onesupporting
confidence: 77%
“…The majority of the 4-OH-midazolam concentrations were below the LLQ (2 ng/mL). The reported metabolic conversion fraction of midazolam to 4-OH-midazolam is 0.03 (19). It is understandable; therefore, that in view of the relatively low midazolam doses in this study, most of the 4-OH-midazolam concentrations were below the LLQ.…”
Section: Pharmacokinetics Of Midazolam After Cardiac Surgerymentioning
confidence: 60%
“…[15] Recent studies on morphine and midazolam in ventilated children reported a possible role of UGT2BT polymorphism in midazolam metabolism. [16,17] Therefore, genotype identi cation may be relevant to predict dosing requirements and treatment e cacy.…”
Section: Which Is the Best Pharmacologic Treatment To Ensure An Adequate Analgesia And Sedation In Children In Icu?mentioning
confidence: 99%